Carbon nanotube modified conductive fluororubber and preparation method thereof
By adding fillers and additives such as carbon nanotubes to the conductive fluoro-rubber, the problem of insufficient conductivity is solved, the conductive and mechanical properties of the conductive fluoro-rubber are improved, and its application potential in various fields is enhanced.
Patent Information
- Application Number
- CN202410124134.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2025-04-15
AI Technical Summary
The current conductive fluoroelastomer has poor electrical conductivity, which limits its application in various fields.
The modified conductive fluoroelastomer is formed by adding carbon nanotubes, metal oxide powder, carbon black, silane coupling agent, anti-aging agent, plasticizer, stearic acid, sulfur vulcanizing agent and accelerator to the fluoroelastomer.
The conductive properties, mechanical properties, weather resistance and processing properties of conductive fluoroelastomer are improved, making it suitable for conductive applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive rubbers, and in particular relates to a carbon nanotube-modified conductive fluororubber and a preparation method thereof. Background Art
[0002] Composite conductive rubber material is a functional composite material made by filling a rubber matrix with conductive fillers. These conductive fillers can be conductive particles, fibers or additives, which have good conductive properties and can form a conductive network in the material. The conductive properties of composite conductive rubber materials can effectively dissipate static electricity, prevent the accumulation of static electricity and the instability of charge. In scenarios where static interference or sparks caused by static electricity need to be prevented, the use of conductive rubber materials can protect the safety of equipment and personnel; at the same time, it can effectively shield electromagnetic radiation and block external electromagnetic waves from interfering with equipment, circuits or electronic components. This material is widely used in electronic equipment, communication equipment and other fields to ensure the stable operation of equipment and reduce the impact of electromagnetic interference on other equipment. Conductive rubber materials have chemical corrosion resistance and can protect equipment or components from chemical corrosion. This is very important for equipment used in the chemical industry or in environments corroded by chemical substances.
[0003] Conductive fluororubber is a fluororubber material with conductive properties. A conductive network is formed by filling conductive particles, fibers or additives in the fluororubber matrix. Conductive fluororubber plays the role of composite conductive rubber materials, including dissipating static electricity, shielding electromagnetic radiation and protecting against electrical corrosion. It effectively prevents the accumulation and instability of static electricity, and reduces the dangers caused by static electricity interference and sparks. At the same time, conductive fluororubber materials can also shield external electromagnetic radiation, ensure the stable operation of equipment, and have the characteristics of chemical corrosion resistance to protect equipment from chemical corrosion. Conductive fluororubber materials play an important role in electrostatic protection, electromagnetic protection and electrical corrosion protection, and are widely used in various fields to reduce or eliminate the hazards caused by electromagnetic interference, radiation and static electricity. However, in the prior art, the conductive performance of conductive fluororubber is poor, which limits its application in various fields.
[0004] Therefore, how to improve the conductivity of conductive fluororubber is a technical problem that technical personnel in this field need to solve urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a carbon nanotube modified conductive fluororubber and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A carbon nanotube modified conductive fluororubber, comprising the following raw materials in parts by weight:
[0008] 100-120 parts of fluororubber, 0.4-0.8 parts of carbon nanotubes, 2-9 parts of metal oxide powder, 23-25 parts of carbon black, 2-3 parts of silane coupling agent, 3-4 parts of antioxidant, 3.5-5 parts of plasticizer, 2-4 parts of stearic acid, 0.3-1 parts of sulfur vulcanizing agent, and 0.8-2.3 parts of accelerator.
[0009] Beneficial effects: The carbon nanotubes in the present invention can form physical or chemical interactions with the surface of fluororubber, enhance the mechanical properties of fluororubber, and improve wear resistance and durability; metal oxide powders can be adsorbed or chemically reacted with fluororubber molecules to improve the thermal conductivity and heat resistance of rubber; carbon black, as a commonly used filler, is evenly dispersed with fluororubber to form a network structure, increasing the strength, hardness and weather resistance of rubber; silane coupling agents can form chemical bonds between fluororubber and fillers, and improve the interaction between fillers and rubber matrix, enhancing the reinforcement effect and aging resistance of rubber; antioxidants can react with fluororubber to form a network structure, thereby improving the strength, hardness and weather resistance of rubber. The molecules interact with each other to form a protective layer, delaying the oxidation and aging process and improving the durability of the rubber; the plasticizer can interact physically or chemically with the fluororubber to increase the softness and plasticity of the rubber, improve the processability and comfort of use; stearic acid can be used as a lubricant to interact with the fluororubber molecules during the rubber mixing process to improve the fluidity and uniformity of the mixing process; the sulfur vulcanizing agent can react with the double bonds in the fluororubber to form a cross-linked structure and enhance the strength and elasticity of the rubber; the accelerator can accelerate the vulcanization reaction of the rubber, increase the vulcanization speed and effect, and enhance the performance of the rubber products.
[0010] Preferably, the carbon nanotubes are single-walled carbon nanotubes;
[0011] The vulcanizing agent is sulfur.
[0012] Beneficial effects: The sulfur in the present invention can undergo a vulcanization reaction with the double bonds in the rubber to form a cross-linked structure. This cross-linked structure can enhance the strength, hardness and wear resistance of the rubber and improve the mechanical properties of the rubber products. The sulfur vulcanization reaction can cause the rubber molecules to form a three-dimensional network structure, improve the elasticity and resilience of the rubber products, and increase their tensile strength and damping properties. The sulfur vulcanization reaction can improve the heat resistance of the rubber, so that it can maintain good performance stability under high temperature conditions. The sulfur vulcanization reaction can also improve the chemical resistance of the rubber products, so that they have good solubility resistance and corrosion resistance. In short, sulfur as a vulcanizing agent can undergo a vulcanization reaction with the double bonds in the rubber to form a cross-linked structure, thereby improving the strength, hardness, wear resistance, elasticity, heat resistance and chemical resistance of the rubber products.
[0013] Preferably, the metal oxide powder is one or any combination of titanium dioxide, tin dioxide, aluminum oxide and zinc oxide.
[0014] Beneficial effects: The present invention selects one or any of titanium dioxide, tin dioxide, aluminum oxide and zinc oxide as metal oxide powder, which is helpful to improve the high temperature resistance, chemical resistance, weather resistance, anti-ultraviolet aging ability, electrical conductivity, mechanical strength, wear resistance and corrosion resistance of rubber products. Among them, titanium dioxide has excellent high temperature resistance and chemical resistance, which can improve the heat resistance and chemical resistance of rubber products. In addition, titanium dioxide also has good ultraviolet absorption ability, which can improve the weather resistance and anti-ultraviolet aging ability of rubber products; tin dioxide can improve the electrical conductivity and mechanical strength of rubber products, enhance the tensile strength and wear resistance of rubber, and secondly, tin dioxide also has excellent high temperature resistance and corrosion resistance, which can improve the durability of rubber products; aluminum oxide has good high temperature resistance, wear resistance and corrosion resistance, which can improve the durability and wear resistance of rubber products, and at the same time, aluminum oxide can also improve the hardness and strength of rubber and enhance the mechanical properties of rubber products; zinc oxide has good high temperature resistance and corrosion resistance, which can improve the durability of rubber products. In addition, zinc oxide also has antibacterial, anti-ultraviolet and anti-aging capabilities, which can improve the weather resistance and anti-aging properties of rubber products.
[0015] Preferably, the carbon black is one or any combination of furnace black, acetylene black and white carbon black.
[0016] Beneficial effects: The present invention selects one or any of furnace black, acetylene black and white carbon black as carbon black fillers, which is helpful to improve the hardness, strength, wear resistance, anti-slip performance, anti-compression deformation ability, durability, stability, weather resistance and anti-aging performance of rubber products. Among them, furnace black is a commonly used type of carbon black, with a large specific surface area and adsorption capacity. Furnace black can increase the hardness, strength and wear resistance of rubber, and improve the anti-slip performance and durability of rubber; acetylene black is a highly crystalline carbon black with high hardness, strength and wear resistance. Acetylene black can increase the hardness and anti-compression deformation ability of rubber and improve the durability and stability of rubber products; white carbon black is a granular substance composed of silicon dioxide, with a large specific surface area and high dispersibility. White carbon black can increase the strength, hardness and wear resistance of rubber, and improve the weather resistance and anti-aging performance of rubber.
[0017] Preferably, the silane coupling agent is one or any several of Si75, A-174, KH570, Si69, Si266, KH550, KH560, and Si75C.
[0018] Beneficial effects: The silane coupling agent in the present invention can form a chemical bond between the filler surface and the rubber molecules, enhance the bonding force between the filler and the rubber matrix, and improve the strength, hardness and wear resistance of the rubber product. The silane coupling agent can improve the dispersibility and distribution uniformity of the filler, effectively increase the interaction between the filler and the rubber, improve the reinforcement effect of the rubber, and increase the strength, stiffness and durability of the rubber product. The silane coupling agent can form a protective film to block the intrusion of oxygen and moisture, slow down the oxidation and aging process of the rubber, and extend the service life of the rubber product. The silane coupling agent can improve the high temperature resistance of the rubber, inhibit the reverse reaction of the vulcanization reaction, and improve the thermal stability and heat resistance of the rubber product. The silane coupling agent can improve the chemical resistance of the rubber product, increase the resistance to some harmful substances, and delay the dissolution or corrosion process of the rubber. In summary, selecting one or any of Si75, A-174, KH570, Si69, Si266, KH550, KH560, and Si75C as a silane coupling agent can help improve the interaction between the filler and the rubber matrix, enhance the reinforcement effect of the rubber, and improve the aging resistance, temperature resistance, and chemical resistance.
[0019] Preferably, the antioxidant is one or any combination of antioxidant MBI, antioxidant 2246, antioxidant E, antioxidant RD, antioxidant 4020, antioxidant DD, antioxidant T501, and antioxidant 4010.
[0020] Beneficial effects: The above antioxidant can inhibit the oxidation and aging process of rubber under external conditions such as oxygen, moisture, and ultraviolet rays, and extend the service life of rubber products. The antioxidant can increase the high temperature resistance of rubber, inhibit the reverse reaction of vulcanization reaction, and improve the thermal stability and heat resistance of rubber products. The antioxidant can interact with the rubber antioxidant, stabilize the performance of the antioxidant, and extend its effective action time in the rubber. The antioxidant can form a protective film to block the intrusion of oxygen and moisture, slow down the oxidation and aging process of rubber, and improve the weather resistance and anti-ultraviolet aging ability of rubber products. The antioxidant can improve the strength, hardness and wear resistance of rubber, and improve the mechanical properties of rubber products. In summary, the selection of the antioxidant in the present invention helps to delay rubber aging, improve heat resistance, protect rubber antioxidants, improve weather resistance and enhance the mechanical properties of rubber.
[0021] Preferably, the plasticizer is one or any combination of diethylhexanoate (DOP), octanoate (DINP), decanoate (DIDP), phthalocyanine blue plasticizer (Pcblueplasticizer), phosphate plasticizers (TBEP, TBP, TEHP), silicone oil plasticizers (PDMS), fatty acid ester plasticizers (such as Cetyl Palmitate, Stearates) and coal tar plasticizers (CTBN).
[0022] Selecting one or any of diethylhexanoate (DOP), octanoate (DINP), decanoate (DIDP), phthalocyanine blue plasticizer (Pc blue plasticizer), phosphate plasticizer (TBEP, TBP, TEHP), silicone oil plasticizer (PDMS), fatty acid ester plasticizer (such as Cetyl Palmitate, Stearates) and coal tar plasticizer (CTBN) as plasticizers can help improve the flexibility, ductility, processing performance, wear resistance, fatigue resistance, low temperature resistance and chemical resistance of rubber products. Plasticizers can reduce the glass transition temperature of rubber products, improve the flexibility and ductility of rubber, and make it easier to process and use. Plasticizers can reduce the melting temperature and viscosity of rubber, improve the fluidity and plasticity of rubber, and improve the processing performance and mold filling performance of rubber. Some plasticizers have lubricating properties, which can reduce the friction between rubber particles and improve the wear resistance and fatigue resistance of rubber. Some plasticizers have low-temperature flexibility, which can improve the elasticity and cold resistance of rubber products in low-temperature environments. Some plasticizers have anti-solvent and chemical resistance properties, which can improve the tolerance of rubber products to some solvents and chemicals.
[0023] Preferably, the accelerator is one or any combination of accelerator DM, accelerator TMTD, accelerator TMTM, accelerator CZ, accelerator MBT, accelerator CBS and accelerator TMT.
[0024] Beneficial effects: The present invention selects one or any several of accelerator DM, accelerator TMTD, accelerator TMTM, accelerator CZ, accelerator MBT, accelerator CBS and accelerator TMT as accelerators, which is helpful to improve the vulcanization efficiency, high temperature resistance, mechanical properties, elastic recovery and processing performance of rubber products. Among them, the accelerator can accelerate the speed and efficiency of the rubber vulcanization reaction, improve the vulcanization degree and vulcanization speed of the rubber product, and can also enhance the high temperature resistance of the rubber, and improve the stability and durability of the rubber product in a high temperature environment. In addition, the accelerator can improve the strength, hardness and wear resistance of the rubber, increase the tensile, compression and shear resistance of the rubber product, and at the same time increase the elasticity and elastic recovery of the rubber, improve the rebound resilience and deformation recovery ability of the rubber product, and the accelerator can improve the fluidity, plasticity and mold filling performance of the rubber, and improve the processing performance and mold forming effect of the rubber.
[0025] A method for preparing carbon nanotube-modified conductive fluororubber comprises the following steps:
[0026] The fluororubber is cut into pieces to remove impurities, mixed evenly with a plasticizer, an antioxidant and an accelerator, and then fed together with the remaining raw materials, and mixed, plasticized, cut and formed to obtain the carbon nanotube modified conductive fluororubber.
[0027] Beneficial effects: The present invention can improve the conductivity, mechanical properties, weather resistance and processing properties of fluororubber by uniformly mixing fluororubber with plasticizer, antioxidant and accelerator, and adding carbon nanotubes as conductive fillers, so that it is suitable for conductive application fields. By adding carbon nanotubes as conductive fillers, the conductivity of fluororubber can be greatly improved, so that it has good conductivity and conductivity, and is suitable for application fields that require conductivity; the addition of plasticizer can improve the flexibility and ductility of rubber, so that it has better strength and wear resistance; the addition of antioxidant can delay the aging process of fluororubber, improve its weather resistance and chemical resistance; the addition of accelerator can accelerate the vulcanization reaction of fluororubber, improve the degree of vulcanization, and enhance the high temperature resistance and anti-aging performance of rubber. After the process steps of mixing and plasticizing, the rubber is evenly mixed with various additives, which can improve the fluidity and plasticity of fluororubber, improve the processing performance of rubber, and make it easier to shape and process.
[0028] Preferably, the mixing comprises the following steps:
[0029] The high temperature and high shearing action of the mixer continuously heats, cuts and squeezes the fluororubber raw rubber and additives to mix evenly. In this process, vulcanizers and other auxiliary agents can be gradually added as needed.
[0030] Preferably, the plasticating comprises the following steps:
[0031] The kneaded mixture was added at 50°C and a mixer speed of 60 r / min, and then the temperature was raised to 80°C at a rate of 3°C / min and stirring was continued for 10 minutes. Vacuum was then evacuated and the negative pressure was maintained at 1 MPa to form sheets and cool them to complete plastication.
[0032] Beneficial effects: In this process, the rubber molecular chain is stretched, broken and reorganized, making it elastic and processable, usually through extrusion, calendering and other methods. During the entire plastication process, it is necessary to strictly control parameters such as temperature, time, shear force, etc. to ensure the modification and processing effect of the rubber molecular chain, and at the same time facilitate subsequent vulcanization or other treatments to obtain the final conductive fluororubber product.
[0033] Preferably, the vulcanization temperature is 170° C. and the time is 20 min.
[0034] The present invention discloses a carbon nanotube modified conductive fluororubber, which uses carbon nanotubes to modify the fluororubber to improve the conductivity, and can solve the problem of insufficient conductivity in the prior art. At the same time, the method can also maintain the excellent mechanical properties of the conductive fluororubber, further enhancing its practicality and reliability. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0037] A carbon nanotube modified conductive fluororubber, comprising the following raw materials in parts by weight:
[0038] 100-120 parts of fluororubber, 0.4-0.8 parts of carbon nanotubes, 2-9 parts of metal oxide powder, 23-25 parts of carbon black, 2-3 parts of silane coupling agent, 3-4 parts of antioxidant, 3.5-5 parts of plasticizer, 2-4 parts of stearic acid, 0.3-1 parts of sulfur vulcanizing agent, and 0.8-2.3 parts of accelerator.
[0039] The vulcanizing agent is sulfur.
[0040] In some preferred embodiments, the metal oxide powder is one or any combination of titanium dioxide, tin dioxide, aluminum oxide and zinc oxide.
[0041] In some preferred embodiments, the carbon black is one or any combination of furnace black, acetylene black and white carbon black.
[0042] In some preferred embodiments, the silane coupling agent is one or any several of Si75, A-174, KH570, Si69, Si266, KH550, KH560, and Si75C.
[0043] In some preferred embodiments, the antioxidant is one or any combination of antioxidant MBI, antioxidant 2246, antioxidant E, antioxidant RD, antioxidant 4020, antioxidant DD, antioxidant T501, and antioxidant 4010. The use of the antioxidant can extend the service life of the conductive fluororubber and prevent rubber aging.
[0044] In some preferred embodiments, the plasticizer is one or any several of diethylhexanoate (DOP), octanoate (DINP), decanoate (DIDP), phthalocyanine blue plasticizer (Pcblueplasticizer), phosphate plasticizer (TBEP, TBP, TEHP), silicone oil plasticizer (PDMS), fatty acid ester plasticizer (such as Cetyl Palmitate, Stearates) and coal tar plasticizer (CTBN). The use of plasticizer can improve the flexibility and ductility of rubber, reduce the glass transition temperature of rubber, and improve the processing properties and plasticity of rubber. Plasticizer can weaken the interaction between rubber molecular chains, increase the plasticity of rubber, and make it easier to process and shape. Plasticizer can also improve the elastic recovery and rebound resilience of rubber, and improve the fatigue resistance and wear resistance of rubber. In addition, the selection and use of plasticizer can also adjust the hardness, strength, temperature resistance and other characteristics of rubber according to specific needs. In a word, the use of plasticizer can provide better processing properties, plasticity and flexibility of performance adjustment for rubber.
[0045] In some preferred embodiments, the accelerator is one or any several of accelerator DM, accelerator TMTD, accelerator TMTM, accelerator CZ, accelerator MBT, accelerator CBS and accelerator TMT. The use of accelerator can accelerate the vulcanization reaction of rubber, improve the vulcanization degree and vulcanization speed of rubber products, and accelerator can be used as a catalyst to promote the sulfur in vulcanizing agent and rubber to react, form a cross-linked structure, thereby improving the strength, hardness and wear resistance of rubber. Using accelerator can also improve the processing properties and mold filling properties of rubber, improve the fluidity and plasticity of rubber, and make it easier to process and shape. In addition, the selection and use of accelerator can also adjust the characteristics such as high temperature resistance, weather resistance and chemical resistance of rubber according to specific needs. In a word, the use of accelerator can improve the vulcanization efficiency, mechanical properties and processing properties of rubber, thereby meeting various application requirements.
[0046] The embodiment of the present invention also discloses a method for preparing carbon nanotube-modified conductive fluororubber, comprising the following steps:
[0047] The fluororubber is cut into pieces to remove impurities, mixed evenly with a plasticizer, an antioxidant and an accelerator, and then fed together with the remaining raw materials, and mixed, plasticized, cut and formed to obtain the carbon nanotube modified conductive fluororubber.
[0048] In a preferred embodiment, the mixing comprises the following steps:
[0049] The high temperature and high shearing action of the mixer continuously heats, cuts and squeezes the fluororubber raw rubber and additives to mix evenly. In this process, vulcanizers and other auxiliary agents can be gradually added as needed.
[0050] In a preferred embodiment, the mastication comprises the following steps:
[0051] Add the kneaded mixture at 50℃ and 60r / min speed of internal mixer, then heat to 80℃ at 3℃ / min and continue stirring for 10min, then evacuate and maintain negative pressure at 1MPa to produce sheets and cool, and the plasticization is completed. In this process, the rubber molecular chain is stretched, broken and reorganized to make it elastic and processable, which is usually completed by extrusion, calendering and other methods. During the entire plasticization process, parameters such as temperature, time, and shear force need to be strictly controlled to ensure the modification and processing effect of the rubber molecular chain, and at the same time facilitate subsequent vulcanization or other treatments to obtain the final conductive fluororubber product.
[0052] In a preferred embodiment, the vulcanization temperature is 170° C. and the time is 20 minutes.
[0053] The raw materials in the examples of the present invention are all purchased from commercial sources.
[0054] Example 1
[0055] A carbon nanotube modified conductive fluororubber, comprising the following raw materials in parts by weight:
[0056] 100 parts of fluororubber, 0.4 parts of single-walled carbon nanotubes, 2 parts of zinc oxide powder, 23 parts of white carbon black, 2 parts of silane coupling agent (Si75), 3 parts of antioxidant (antioxidant RD and antioxidant DD are mixed in a mass ratio of 1:1), 3.5 parts of plasticizer (coal tar plasticizer CTBN), 2 parts of stearic acid, 0.3 parts of sulfur, and 0.8 parts of accelerator (accelerator CZ).
[0057] A method for preparing carbon nanotube-modified conductive fluororubber comprises the following steps:
[0058] (1) Pretreatment: Chop the fluororubber raw rubber into appropriate blocks, remove impurities and improve plasticity, and then mix it evenly with an appropriate amount of plasticizer, antioxidant, accelerator, etc.
[0059] (2) Material feeding and mixing: The pre-treated fluororubber raw rubber and other additives are fed into a rubber mixer for mixing. Through the high temperature and high shearing action of the mixer, the fluororubber raw rubber and the additives are continuously heated, cut and extruded to make them evenly mixed. During this process, vulcanizers and other auxiliary agents can be gradually added as needed.
[0060] (3) Plasticizing and vulcanization: add the kneaded mixture at 50°C and a mixer speed of 60r / min, then heat it to 80°C at a speed of 3°C / min and continue stirring for 10min, then evacuate and maintain the negative pressure at 1MPa to produce a sheet, and cool it to a temperature below 40°C to obtain a masterbatch; then heat it to 170°C for vulcanization for 20min, and after the vulcanization is completed, remove the glue, produce a sheet, cool it, and let it stand for 2 days to obtain the plasticized conductive fluororubber;
[0061] (4) Cutting and molding: The conductive fluororubber plasticized in step (3) is cut into blocks of appropriate size as required, and then subjected to processes such as calendering, extrusion, and pressing to produce carbon nanotube-modified conductive fluororubber.
[0062] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube-modified conductive fluororubber are tested, and finally the tensile strength is 20.6MPa, the elongation at break is 448.9%, and the conductivity is 1.25×10 -5 S / cm.
[0063] Example 2
[0064] A carbon nanotube modified conductive fluororubber, comprising the following raw materials in parts by weight:
[0065] 110 parts of fluororubber, 0.8 parts of single-walled carbon nanotubes, 9 parts of zinc oxide powder, 25 parts of white carbon black, 3 parts of silane coupling agent (Si75), 4 parts of antioxidant (antioxidant RD and antioxidant DD are mixed in a mass ratio of 1:1), 5 parts of plasticizer (coal tar plasticizer CTBN), 4 parts of stearic acid, 1 part of sulfur, and 2.3 parts of accelerator (accelerator CZ).
[0066] A method for preparing carbon nanotube-modified conductive fluororubber is the same as that in Example 1.
[0067] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube modified conductive fluororubber are tested, and finally the tensile strength is 19.8MPa, the elongation at break is 400.8%, and the conductivity is 1.85×10 -5 S / cm.
[0068] Example 3
[0069] A carbon nanotube modified conductive fluororubber, comprising the following raw materials in parts by weight:
[0070] 120 parts of fluororubber, 0.8 parts of single-walled carbon nanotubes, 9 parts of zinc oxide powder, 25 parts of white carbon black, 3 parts of silane coupling agent (Si75), 4 parts of antioxidant (antioxidant RD and antioxidant DD are mixed in a mass ratio of 1:1), 5 parts of plasticizer (coal tar plasticizer CTBN), 4 parts of stearic acid, 1 part of sulfur, and 2.3 parts of accelerator (accelerator CZ).
[0071] A method for preparing carbon nanotube-modified conductive fluororubber is the same as that in Example 1.
[0072] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube modified conductive fluororubber are tested, and finally the tensile strength is 18.6MPa, the elongation at break is 410.8%, and the conductivity is 1.96×10 -5 S / cm.
[0073] Comparative Example 1
[0074] A conductive fluororubber, which is different from Example 1 in that it does not include single-walled carbon nanotubes. Other raw materials and addition amounts are the same as those in Example 1.
[0075] A method for preparing conductive fluororubber is the same as that in Example 1.
[0076] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube-modified conductive fluororubber are tested, and finally the tensile strength is 16.1MPa, the elongation at break is 300%, and the conductivity is 1.22×10 -5 S / cm.
[0077] Comparative Example 2
[0078] A conductive fluororubber, which is different from Example 1 in that white carbon black is not included. Other raw materials and addition amounts are the same as those in Example 1.
[0079] A method for preparing conductive fluororubber is the same as that in Example 1.
[0080] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube-modified conductive fluororubber are tested, and finally the tensile strength is 19.1MPa, the elongation at break is 428%, and the conductivity is 1.15×10 -5 S / cm.
[0081] Comparative Example 3
[0082] A conductive fluororubber, which is different from Example 1 in that zinc oxide powder is not included. Other raw materials and addition amounts are the same as those in Example 1.
[0083] A method for preparing conductive fluororubber is the same as that in Example 1.
[0084] According to the tensile test using a tensile testing machine, the tensile force is gradually applied at a certain tensile rate, the stress-strain curve is recorded, and the tensile strength and elongation at break are obtained from the curve. And the conductivity test is performed using a four-probe resistivity tester or a conductivity tester. The test electrode is contacted to the surface of the sample, a constant current is applied, the voltage difference is measured, and the conductivity is obtained by calculation. The tensile strength, elongation at break and conductivity of the obtained carbon nanotube-modified conductive fluororubber are tested, and finally the tensile strength is 19.2MPa, the elongation at break is 420%, and the conductivity is 1.08×10 -5 S / cm.
[0085] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A carbon nanotube modified conductive fluororubber, characterized in that: The invention comprises the following raw materials in parts by weight: 100-120 parts of fluororubber, 0.4-0.8 parts of carbon nanotubes, 2-9 parts of metal oxide powder, 23-25 parts of carbon black, 2-3 parts of silane coupling agent, 3-4 parts of antioxidant, 3.5-5 parts of plasticizer, 2-4 parts of stearic acid, 0.3-1 parts of vulcanizer and 0.8-2.3 parts of accelerator.
2. The carbon nanotube-modified conductive fluororubber according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes; The vulcanizing agent is sulfur.
3. The carbon nanotube-modified conductive fluororubber according to claim 1, characterized in that: The metal oxide powder is one or any combination of titanium dioxide, tin dioxide, aluminum oxide and zinc oxide.
4. The carbon nanotube-modified conductive fluororubber according to claim 1, characterized in that: The carbon black is one or any combination of furnace black, acetylene black and white carbon black.
5. The carbon nanotube-modified conductive fluororubber according to claim 1, characterized in that: The silane coupling agent is one or any several of Si75, A-174, KH570, Si69, Si266, KH550, KH560 and Si75C.
6. The carbon nanotube modified conductive fluororubber according to claim 1, characterized in that: The antioxidant is one or any combination of antioxidant MBI, antioxidant 2246, antioxidant E, antioxidant RD, antioxidant 4020, antioxidant DD, antioxidant T501 and antioxidant 4010.
7. The carbon nanotube-modified conductive fluororubber according to claim 1, characterized in that: The plasticizer is one or any combination of diethylhexanoate, octanoate, decanoate, phthalocyanine blue plasticizer, phosphate plasticizer, silicone oil plasticizer, fatty acid ester plasticizer and coal tar plasticizer.
8. The carbon nanotube modified conductive fluororubber according to claim 1, characterized in that: The accelerator is one or any combination of accelerator DM, accelerator TMTD, accelerator TMTM, accelerator CZ, accelerator MBT, accelerator CBS and accelerator TMT.
9. A method for preparing a carbon nanotube-modified conductive fluororubber according to any one of claims 1 to 8, characterized in that: The following steps are involved: The fluororubber is cut into pieces to remove impurities, mixed evenly with a plasticizer, an antioxidant and an accelerator, and then fed together with the remaining raw materials, and mixed, plasticated, vulcanized, cut and formed to obtain the carbon nanotube-modified conductive fluororubber.
10. The method for preparing carbon nanotube-modified conductive fluororubber according to claim 9, characterized in that: The plasticating comprises the following steps: Add the kneaded mixture at 50°C and 60r / min speed of internal mixer, then heat to 80°C at a speed of 3°C / min and continue stirring for 10min, then evacuate and maintain the negative pressure at 1MPa to form sheets and cool, thus completing the plastication; The vulcanization temperature is 170° C. and the vulcanization time is 20 minutes.
Citation Information
Cited By
Full-sea-depth antenna packaging assembly and packaging method thereof
CN120601119A